SCX-1500 Thousand-Line Digital SPC PBX - Zhang Zhaoxiang and Gu Jiaaxia (Tongxin xuebao)
The system architecture, hardware and software constructions of SOX-1500 digital SPC PBX are briefly described in the paper.